2007
DOI: 10.1111/j.1600-065x.2007.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecto‐calreticulin in immunogenic chemotherapy

Abstract: The conventional treatment of cancer relies upon radiotherapy and chemotherapy. Such treatments supposedly mediate their effects via the direct elimination of tumor cells. Nonetheless, there are circumstances in which conventional anti-cancer therapy can induce a modality of cellular demise that elicits innate and cognate immune responses, which in turn mediate part of the anti-tumor effect. Although different chemotherapeutic agents may kill tumor cells through an apparently homogeneous apoptotic pathway, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
208
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(216 citation statements)
references
References 70 publications
2
208
0
3
Order By: Relevance
“…The natural tumor growth (without treatment) was not influenced by the autophagy competence of the host. Moreover, a single intraperitoneal injection of MTX, that was administered when the tumor reached a surface of 25 mm 2 , was able to reduce tumor growth indistinguishably in WT, Atg4b −/- and Becn1 +/- mice (Figure 2A-C). In conclusion, it appears that the autophagy competence of the host does not impact the efficacy of ICD-inducing chemotherapy.
10.1080/2162402X.2018.1498285-F0002Figure 2. Systemic autophagy deficiency does not impact on the efficacy of anthracycline-based immunogenic chemotherapy.
…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The natural tumor growth (without treatment) was not influenced by the autophagy competence of the host. Moreover, a single intraperitoneal injection of MTX, that was administered when the tumor reached a surface of 25 mm 2 , was able to reduce tumor growth indistinguishably in WT, Atg4b −/- and Becn1 +/- mice (Figure 2A-C). In conclusion, it appears that the autophagy competence of the host does not impact the efficacy of ICD-inducing chemotherapy.
10.1080/2162402X.2018.1498285-F0002Figure 2. Systemic autophagy deficiency does not impact on the efficacy of anthracycline-based immunogenic chemotherapy.
…”
Section: Resultsmentioning
confidence: 94%
“…In mouse models, tumor growth reduction by chemotherapeutic agents often is dependent on T lymphocytes, meaning that tumors evolving in mice that lack T cells do not decrease their progression upon injection of cytotoxicants. 1,2 One efficient way to stimulate such therapeutically relevant antitumor immune responses consists in the induction of immunogenic cell death (ICD). Anthracyclines (such as mitoxantrone, MTX) are able to stimulate ICD, a modality of cell death that is preceded or accompanied by the release of danger-associated molecular patterns (DAMPs), which alert innate effectors for the initiation of a cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…2,9,38 This 'eat-me' signal promotes phagocytosis by DCs, thereby facilitating their tumor antigen presentation and incitement of TAA-specific cytotoxic T cells. 2,47 It has been shown that blockade of CRT inhibits phagocytosis of anthracycline-treated tumor cells by DCs and impairs their immunogenicity in mice. 2,47 In general, CRT exposure during ICD is an earlier process occurring within a few hours than PS externalization.…”
Section: Calreticulin Exposurementioning
confidence: 99%
“…2,47 It has been shown that blockade of CRT inhibits phagocytosis of anthracycline-treated tumor cells by DCs and impairs their immunogenicity in mice. 2,47 In general, CRT exposure during ICD is an earlier process occurring within a few hours than PS externalization. 48 The ecto-CRT induction capacity of ICD inducers has been shown to depend on the properties of ER stress and ROS production.…”
Section: Calreticulin Exposurementioning
confidence: 99%
“…The attraction of leukocytes into premalignant and malignant lesions is dictated by multiple soluble factors including so-called danger-associated molecular patterns (DAMPs) that include extracellular nucleotides and nucleosides (with ATP as a prominent chemotactic factor for myeloid cells), proteins that are usually confined in intracellular compartments yet are released from stressed, dying and dead cells (such as annexin-1, ANXA1; calreticulin, CALR, F-actin, and high molecular group protein-1, HMGB1) 1217 and proteins that are actively secreted by cancer or stromal cells, in particular chemokines (C-C motif chemokine ligand 1 to 9 and 11 to 28, CCL1-9, CCL11-28; X-C motif chemokine ligand 1 and 2, XCL1 and 2; C-X-C motif chemokine ligand 1 to 17, CXCL1-17; C-X 3 -C motif chemokine ligand 1, CX3CL1). 18 These factors act on a series of receptors, such as the adenosine receptor family AdoR (ADOR A1, A2A, A2B and A3), metabotropic purinergic receptors (P2RY1, 2, 4, 6, 8 and 10 to 14), ionotropic purinergic receptors (P2RX1 to 7), formylpeptide receptors (FPR1 to FPR3) and chemokine receptors (XCR1, CXCR1 to 7, CX2CR1, CCR1 to 10, CCRL1 and 2) to induce the chemotaxis of different leukocyte subtypes into the tumor.…”
Section: Introductionmentioning
confidence: 99%